1981
DOI: 10.1128/iai.31.1.199-207.1981
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the bursa of Fabricius on the pathogenesis of Marek's disease

Abstract: A series of experiments was conducted to study the influence of embryonal bursectomy (EBX) on the early and late pathogenesis of Marek's disease (MD). The early lytic infection in the lymphoid organs normally associated with oncogenic MD virus infection in intact chickens was not seen in EBX chickens. Therefore, the damage to the immune system was minimal. EBX chickens also had lower viremia levels, higher lymphocyte responses to mitogens, and a lower or delayed MD mortality when compared with intact chickens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 26 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…Shek et al (1983) showed that bursa-derived lymphocytes (B cells) were the predominant cell type involved in the early cytolytic infection with MDV in vivo and that subsequent latent infections were found mostly in Ia-bearing non-B lymphocytes, presumably T cells. This fitted the pattern suggested by an earlier study by Schat et al (1981a) in which embryonally bursectomized chickens, free of B cells, failed to exhibit early cytolytic MDV infection but did develop latent infection and tumors. Calnek et al (1982) studied in vitro infection of spleen cells and learned that B cells were the major target of cytolytic infection in that system as well.…”
supporting
confidence: 89%
“…Shek et al (1983) showed that bursa-derived lymphocytes (B cells) were the predominant cell type involved in the early cytolytic infection with MDV in vivo and that subsequent latent infections were found mostly in Ia-bearing non-B lymphocytes, presumably T cells. This fitted the pattern suggested by an earlier study by Schat et al (1981a) in which embryonally bursectomized chickens, free of B cells, failed to exhibit early cytolytic MDV infection but did develop latent infection and tumors. Calnek et al (1982) studied in vitro infection of spleen cells and learned that B cells were the major target of cytolytic infection in that system as well.…”
supporting
confidence: 89%
“…Indeed, this process was recapitulated in vitro by the co-culture of MDV-infected B cells with CD4 + T cells [99]. However, other studies showed that the depletion of B cells by chemicals [100], X-ray irradiation, and/or surgical removal of the bursa of Fabricius [98,101] did not consistently lead to the reduction in viral replication in chickens [92], rendering the role of B cells in MDV pathogenesis inconclusive. Recently, using Ig heavy chain J gene segment knockout (JH-KO) chickens that are deficient in mature and peripheral B cells, Bertzbach et al showed that in the absence of B cells, viral load in the blood of infected animals was not altered.…”
Section: B Cellsmentioning
confidence: 99%
“…the ellipsoidassociated cells in the spleen (20,22,23,24). Then the virus is transferred to B lymphocytes, which become lethally infected and infect T lymphocytes, which can be transformed by MDV (25,26). Supposedly, MDV infects T lymphocytes between day 7 and 14 after infection, which coincides with the period of depletion of thymocytes by CAV.…”
Section: Score Of Infiltrates Atmentioning
confidence: 99%